Gestão da manutenção predial: definição de práticas e ferramentas a partir de conceitos aplicados da indústria 4.0 na construção civil - Timafejn, Matheus Inglês (Universidade Federal de São Carlos, 2021)
With the advent of the Fourth Industrial Revolution, also known as Industry 4.0, new technologies are being developed and implemented. In Civil Engineering, great changes have been taking place and it is important to raise a panorama of these new technologies in order to stimulate the interest, creation, adoption and development of these technological innovations. Building maintenance is a branch of civil construction that has considerable space for evolution in its studies and innovations. The phase of use and operation is the longest and bigger cost in the life cycle of a building, so the maintenance management requires methods and tools to assist this process, such as the use of BIM, drones, sensors, among others. The present work seeks to gather tools, technologies and methods characteristic and coming from industry 4.0 used in the management of building maintenance. For such used a methodology of research, extraction, processing and analysis of bibliographical data of articles, theories, among others, known as RBS (Systematic Bibliographical Revision), which aims to compile and to create analytical basement on the subject. The intention of the research is to favor each time more the use and applications of these techniques, since the results of their uses involve increase of productivity, quality, precision and reduction of deadlines. In addition, the improvement and evolution of building maintenance and its management will promote improvements in the performance of construction systems, reduction of the deterioration processes and costs of recovery, and thus increase the useful life of the building.
Building maintenance management: definition of practices and tools based on applied concepts from industry 4.0 in civil construction
Keywords: Indústria 4.0; Engenharia civil; Manutenção; Gestão; Tecnologias; BIM; RBS; Industry 4.0; Civil engineering; Maintenance; Management; Technologies; SBR; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL